PENYELESAIAN SENGKETA TERHADAP HAK MILIK ATAS TANAH MELALUI MEDIASI PADA PENGADILAN NEGERI PEKANBARU - Dede Suhendra; Maryati Bachtiar; Riska Fitriani (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2018)
Mediasi is a form of dispute settlement which brought together both sides that there is a difference ofunderstanding adn involving third parties for finding a solution or a way out of the problems faced. Mediasithis is where two sides can voice opinions of each of the problems that exist and is excepted that the peacebetween the two sides. The dispute over property rightsThis type of research can be classified in this type of research sociological (empiris), where is theresearch of sociologists (empiris), which is in an effort saw the influence of the law positively to the lives ofordinary people, because in this study author immediately embarked on a study on the location or place,which in order ti provide a comprehensive and clear about the problem investigated. The research wascarried out in the District Court of First Class IA, Pekanbaru, while the population and the sample is awhole the parties with regards to the problem, which in this study, the sources of data used, the primary,secondary, tertiary, techniques of collecting data in this study with interviews and review literature.From the results of this study can be concluced that the District Courtof First Class IA is not mediatein accordance with the PERMA that applies. This is evidenced by not requred to his parties concerning tofollow the mediation, while in PERMA No. 1 Year 2008 on the procedure of Mediation in the Court requiresthe parties to participate in mediation. The factors in the opposite direction of mediation and that is the lackof good faith of the parties and legal counsel. The failure of mediation is due to the judges mediators, thelack of socialization of mediation and the number of judges mediators.